Retroperitoneal bronchogenic cyst resembling an adrenal tumor with high levels of serum carbohydrate antigen 19-9: A case report. Issue 31 (August 2017) - Wang, Min; He, Xu; Qiu, Xia; Tian, Chuan; Li, Jian; Lv, Mingnan
Abstract: Rationale: Retroperitoneal bronchogenic cysts without specific clinical manifestations are extremely rare and difficult to diagnose preoperatively and are easily misdiagnosed as left adrenal or pancreatic tumors. Patient concerns: A 48-year-old woman with the chief complaint of obscure epigastric pain for 1 month and with no other gastrointestinal symptoms and no significant medical history. The patient had signed informed consent for publication of this case report. Diagnosis: The serum level of carbohydrate antigen 19-9 (CA 19-9) in the patient was >1200 U/mL, which far exceeded the normal level of <37 U/mL. Computed tomography (CT) initially suggested the presence of an adrenal tumor. However, endoscopic ultrasound (EUS) showed that the adrenal gland had an intact capsule and that the mass originated in the retroperitoneal space and did not involve the paranephros. Interventions: Surgical resection was performed on the patient. Outcomes: Histopathological examination demonstrated that the mass was a retroperitoneal bronchogenic cyst. At the 2-month postoperative follow-up, the level of CA 19-9 had returned to normal. Lessons: EUS appears to be superior to CT because it clearly delineated the mass from the surrounding structures of the retroperitoneal region. EUS-fine needle aspiration can be used for diagnosis or determining whether the mass is malignant or benign. To the best of our knowledge, retroperitoneal bronchogenic cysts with significantly elevated serum CA 19-9 have not been reported. Measurement of serum CA 19-9 may be helpful in the diagnosis of retroperitoneal bronchogenic cysts. However, this was a rare case, and the mechanism behind CA 19-9 elevation is not clear and needs further investigation.